2022
DOI: 10.3390/ijerph19063438
|View full text |Cite
|
Sign up to set email alerts
|

Community Knowledge about Autism Spectrum Disorder in the Kingdom of Saudi Arabia

Abstract: Objectives: To explore the knowledge of the general community in Saudi Arabia about autism spectrum disorder. Method: A cross-sectional study was conducted for the period between June and September 2021 in Saudi Arabia using an online questionnaire tool. The questionnaire tool was developed based on a literature review. The questionnaire tool consists of 34 items that assess knowledge about autism spectrum disorder in terms of its etiology, autistic patient features, autistic children’s abilities and needs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…A much higher level of parental knowledge regarding autism was reported by Kandice J. Benallie 20 where 43.9% of the parents showed good knowledge levels regarding the disorder. Similarly low levels of knowledge among parents was detected in Pakistan by Anwar et al 21 who reported that poor knowledge scores, with a mean score of 5.59 in the section concerning correct opinions on autism and that of 6.84 in the section testing knowledge of signs and symptoms.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A much higher level of parental knowledge regarding autism was reported by Kandice J. Benallie 20 where 43.9% of the parents showed good knowledge levels regarding the disorder. Similarly low levels of knowledge among parents was detected in Pakistan by Anwar et al 21 who reported that poor knowledge scores, with a mean score of 5.59 in the section concerning correct opinions on autism and that of 6.84 in the section testing knowledge of signs and symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…During the COVID-19 pandemic and quarantine all autistic children stayed in their homes with no contact with their teachers which made the role of their families to teach them and care about them more important due to the absence of their teacher's effect. 12,19 A much higher level of parental knowledge regarding autism was reported by Kandice J. Benallie 20 where 43.9% of the parents showed good knowledge levels regarding the disorder. Similarly low levels of knowledge among parents was detected in Pakistan by Anwar et al 21 who reported that poor knowledge scores, with a mean score of 5.59 in the section concerning correct opinions on autism and that of 6.84 in the section testing knowledge of signs and symptoms.…”
Section: Discussionmentioning
confidence: 89%
“…The European Research Journal 2023 been rising in recent decades, and it has been determined that boys are at 4.2 times more risk than girls [2]. It is thought that the increasing prevalence, developing technology and facilitating access to information, and the fact that families seek to diagnose their children are compelling.…”
Section: Early Onlinementioning
confidence: 99%
“…ASD was defined separately from other childhood diseases by the American Psychiatric Association in 1980 and was classified as five diseases in 1994: Autism, Asperger's Syndrome, Atypical Autism, Childhood Disintegrative Disorder, and Rett Syndrome. However, in 2013, Rett Syndrome was excluded from this category, and all were defined as ASD based on social communication and isolatedrepetitive sensory activities [2]. While one out of 59 children is diagnosed with ASD in the United States, this rate is estimated to be around 1% globally [3,4].…”
mentioning
confidence: 99%
“…Certain troubles are linked to food discernment and food refusal and are more likely focused than those related to mealtime (Bonsall et al, 2021;Kang et al, 2022). Recent studies from Saudi Arabia have shown relatively low awareness levels of autism (Sabbagh et al, 2021;Abualhommos et al, 2022;Alyami et al, 2022).…”
Section: Medical Sciencementioning
confidence: 99%